The Effect of COVID-19 Lockdown on Mobility and Traffic Accidents: Evidence from Louisiana - Stephen R. Barnes; Louis-Philippe Beland; Jason Huh; Dongwoo Kim (Global Labor Organization (GLO), 2020)
We use a regression discontinuity design to study the effect of the COVID-19 lockdown on mobility and traffic accidents. Based on data from Google Community Mobility reports and Uniform Traffic Crash Report from the Louisiana Department of Transportation and Develop- ment (LaDOTD), we find that the stay-at-home order led to a large decrease in traffic accidents (-47 percent). In particular, we find a large decrease in accidents involving injury (-46 percent), distracted drivers (-43 percent), and ambulances (-41 percent). We also find evidence of a change in the composition of accidents, with more incidents involving individuals aged 25 to 64, male, and nonwhite drivers. Interestingly, we find no impact on ambulance response time, despite lower traffic. Finally, we document a large decrease in mobility in Louisiana. Our results have important policy implications for traffic management policies.
Keywords: R20; R41; R42; R48; H41; D62; 330; COVID-19; Lockdown; Accidents; Traffic Management; Regression Discontinuity